1991
DOI: 10.1111/j.1479-828x.1991.tb02807.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared Antenatal Care in Brisbane

Abstract: The prevalence of antenatal care shared between general practitioner (GP) and public hospital services in Brisbane, and its acceptability to patients was assessed. Responses to questionnaires put to women in the immediate puerperium of the public wards of 2 major teaching hospitals are presented. Antenatal shared-care was undertaken in 54% of pregnancies. Indications of advantages for women to undergo antenatal shared-care were identified with convenience of appointment time, and decreased travel and waiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In conclusion, at a time when metropolitan GPs view the future of GP obstetrics in public hospitals with pessimism (ll), shared obstetric care is a model of care that provides a satisfying and valuable role for the GP and an opportunity for close collaboration between GPs, obstetricians and midwives. It has the potential to become the predominant model of care for women of low obstetric risk in the public hospital system with the benefits of increased satisfaction for women (3,12) without compromising perinatal mortality, and financial savings to public hospitals. However, before this can occur, it is important that further evaluation be undertaken to compare other models of shared care, particularly those affiliated with other maternity hospitals in Australia, as GPs in this study have indicated that there may be inadequacies in other shared care programmes that are not present in the Royal Women's Hospital programme.…”
Section: Further Role For Gp Obstetricsmentioning
confidence: 99%
“…In conclusion, at a time when metropolitan GPs view the future of GP obstetrics in public hospitals with pessimism (ll), shared obstetric care is a model of care that provides a satisfying and valuable role for the GP and an opportunity for close collaboration between GPs, obstetricians and midwives. It has the potential to become the predominant model of care for women of low obstetric risk in the public hospital system with the benefits of increased satisfaction for women (3,12) without compromising perinatal mortality, and financial savings to public hospitals. However, before this can occur, it is important that further evaluation be undertaken to compare other models of shared care, particularly those affiliated with other maternity hospitals in Australia, as GPs in this study have indicated that there may be inadequacies in other shared care programmes that are not present in the Royal Women's Hospital programme.…”
Section: Further Role For Gp Obstetricsmentioning
confidence: 99%
“…The majority of women receiving other types of antenatal care reported no knowledge of shared care, and only one-third of them were not interested in finding out about it in the event of a subsequent pregnancy. Ratten & McDonald (1992) described the Melbourne shared care program as having operated for 'many years' (p 297) and including 270 general practitioners, and although Del Mar et al (1991) did not mention the history or size of shared antenatal care in Brisbane hospitals, they did comment that a loose definition of shared care status may have contributed to the relatively high proportion of shared care patients reported in their study.…”
Section: Discussionmentioning
confidence: 74%
“…The proportion of patients receiving shared obstetric care has been reported to range up to 24␣ per cent (Ratten & McDonald 1992) or even 54␣ per cent (Del Mar et al 1991) in Australian public hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPs can provide safe, caring and cost-effective obstetric care (43). Most general practice obstetrics takes the form of shared-care, andin Brisbane at leastmost public hospital maternity patients use this form of care (6). Shared-care obstetrics is the cooperative arrangement between an obstetric hospital and community clinician for providing antenatal and postnatal care (7,8).…”
mentioning
confidence: 99%